Japanese Capitalism and Income Inequality: A Comparison with Great Britain - Furuoka, Fumitaka (AEI Insights, 2021)
In his seminal book, Thomas Piketty points an alarming concentration and a serious income inequality in the 21st century (Piketty, 2014). He warned that capital has played an increasingly dominant role in the economic development, and that national wealth is shared by a limited number in the upper class. This paper chooses Japan as a case study to examine the wealth distribution in the country. There are two main research objectives in this paper. The first main objective of this paper is to examine the main characteristics of Japanese capitalism. The second objective is to compares Japanese capitalism with typical free-market capitalism in Europe; British capitalism. This paper point out that there is a serious income inequality in Great Britain, following its conservative revolution in the middle of the 1980s. By contrast, this paper also argues that national wealth in Japan is more equally distributed than Great Britain. Thus, this paper concludes that Japan does not seem to follow the development path of Great Britain so to become a new patrimonial capitalism.